Pengaruh Penerapan Model Pembelajaran Project Based Learning (PjBL) Terintegrasi STEM Terhadap Kemampuan Berpikir Kritis dan Kreativitas Siswa SMAN 1 Pademawu - Siadah, Kurniatus; Tobing, Victor Maruli Tua L; Isman, Soubar (Peneliti.net, 2024)
This research is a quantitative study aiming to examine the effect of implementing the Project-Based Learning (PjBL) model integrated with STEM on the critical thinking and creativity skills of students at SMAN 1 Pademawu. The sample consisted of 60 respondents, including 28 students in the control class and 32 students in the experimental class. The sampling technique employed was random sampling. Data collection was conducted by administering pre-tests and post-tests consisting of five essay questions that assessed critical thinking and 24 questionnaire items measuring creativity. Validation and analysis were performed using validity and reliability tests, normality and homogeneity tests, t-tests, and N-Gain tests, all analyzed using SPSS version 27. The test results indicate: 1) Significant Influence: The implementation of the STEM-integrated Project-Based Learning (PjBL) model significantly influenced students' critical thinking, as indicated by an independent samples test significance value for critical thinking (Sig. 2-tailed) < 0.001 < 0.05 and for creativity (Sig. 2-tailed) < 0.001 < 0.05. These results indicate significant differences in the average critical thinking and creativity scores between the control and experimental classes after the intervention; 2) Improvement in Skills: The STEM-integrated PjBL model significantly improved students' critical thinking and creativity, as evidenced by the descriptive N-Gain mean for critical thinking being 93.9591 in the experimental class > 53.8191 in the control class, and the mean for creativity being 81.6743 in the experimental class > 21.6814 in the control class; 3) Effectiveness: The implementation of the STEM-integrated Project-Based Learning (PjBL) model was categorized as effective in enhancing students' critical thinking and creativity based on Hake’s R.R. criteria, with critical thinking scores of 93.9591 > 76 and creativity scores of 81.6743 > 76.